Pengaruh FDR, CAR dan NPF Terhadap Profitabilitas Bank Umum Syariah Periode 2018-2022 - Muhamad Ifan Permana Ifan (Journal of Islamic Economic and Business Studies, 2023)
The research was conducted to analyze the effect of FDR, CAR, and NPF on Profitability by measuring Return On Assets (ROA) at Islamic Commercial Banks registered with the Financial Services Authority (OJK). They used quantitative research from the results of collecting quarterly financial report data for the 2018-2022 period at Bank Muamalat Indonesia (BMI), Bank Bukopin Syariah, Bank Mega Syariah, and BCA Syariah. The research data analysis technique used panel data regression analysis with the help of E-Views 10 software with the Chow and Hausman test methods, then the Fixed Effect Model (FEM) test was selected. The testing hypothesis used the partial-t test, simultaneous-F test, and the coefficient of determination test (R2). Hypothesis test results Partially, FDR has a positive and significant effect, while CAR and NPF have a negative and significant effect. The results of the simultaneous-F test explain that FDR, CAR, and NPF simultaneously influence ROA. The coefficient of determination test (R2) results clarify that 80% of FDR, CAR, and NPF variables affect profitability in Islamic commercial banks. The remaining 20% ​​are influenced by variables not included in this study.